DIAGNOSTIC EFFICACY OF CELL BLOCK METHOD VERSUS CONVENTIONAL SMEAR CYTOLOGY IN MALIGNANT PLEURAL AND ASCITIC EFFUSIONS (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Cytological examination of serous effusions is the primary method for detecting malignant cells in pleural and ascitic fluids. Conventional smear cytology has limitations in sensitivity and architectural detail. The cell block technique, by concentrating cellular material into paraffin-embedded sections, offers superior morphological preservation.Aims and Objectives: To compare the diagnostic efficacy of cell block preparation with conventional smear cytology in the detection of malignancy in pleural and ascitic effusions.Materials and Methods: The study was conducted in Geetanjali Medical College and Hospital, Udaipur, over 18 months, in clinically suspected malignant cases. Eighty serous effusion specimens including 53 pleural and 27 ascitic fluid samples were processed by conventional smear cytology method as well as cell block. Specimens were classified as positive, suspicious, or negative for malignancy, after examination of morphological characteristics, and compared between conventional cytology smears and cell block sections.Results: The mean patient age was 58.4 ± 14.0 years (range 13–85 years). Cell block detected malignancy in 75% of cases versus 61.3% by conventional smear (p